Impact on outcome of different etiologies, baseline degree and improvement of mitral regurgitation in patients with aortic stenosis who underwent transcatheter aortic valve replacement. (8th February 2021) - Melillo, F; Putorti, F; Ancona, F; Stella, S; Capogrosso, C; Ingallina, G; Montorfano, M; Colombo, A; Agricola, E
Abstract: Funding Acknowledgements: Type of funding sources: None. Background -  Mitral regurgitation (MR) is a frequent finding in patients with aortic stenosis (AS). Moderate or severe MR is present in up to one-third of pts undergoing TAVR and it is a negative prognostic factor as well as the presence of residual MR after TAVR. However, whether different etiologies/mechanisms of MR have different effects on outcome and MR degree changes after TAVR is yet unknown. Aim – The aim of the study is to evaluate the prognostic impact of baseline MR degree and its changes after TAVR procedures according to different etiologies of MR in patients who underwent TAVR. Methods - We performed a retrospective observational study on a cohort of patients who underwent TAVR between January 2015 and December 2019. During the index period 947 pts underwent TAVR. To better characterize the mechanism of MR only pts with pre-procedural 3D transesophageal echocardiographic and at least one follow-up available study were included. The final study population consisted of 224 pts. MR severity was evaluated by multiparametric approach and classified in 4 degrees. The study population was further divided in 4 groups: Group I: fibro-calcific degeneration of the leaflets (78.6% pts); 2. Group II: prolapse or flail (4.4% pts); Group III: functional MR (FMR) due to leaflets tethering (5.6% pts); Group IV: FMR due to annular dysfunction or dilatation (11.3% pts). Primary outcome was all-cause of death. Results and Discussion – MR was absent in 15 pts (6.7%), mild in 79 pts (35.7%), mild-to-moderate in 109 in pts (49.3%), moderate-to-severe in 7 pts (3.1%) and severe in 11 pts (4.9%). Patients with > moderate MR degree at baseline had a worse outcome than patients with < moderate MR degree (p log rank = 0.029). FMR (groups III and IV) was associated with better outcome than organic MR (groups I and II) (p log rank = 0.035). Moreover, group IV showed a better outcome compared groups I (p log rank = 0.047) and II (p log rank = 0.038). Patients who showed improvement of MR of at least 1 degree post TAVR showed better outcome compared to patients without improvement (p log rank = 0.04). At multivariate analysis, including pre procedural MR > 2+, pre procedural TR > 2+, organic vs functional etiology and MR improvement after TAVR as covariates, only baseline MR > moderate was an independent predictor of mortality (HR 6.3; 95% CI 1.4 -27.0; p < 0.001). Conclusion - This study confirms the prognostic role of the baseline degree of MR in patients with AS undergoing TAVR. Moreover, this is the first study demonstrating that FMR due to annular dilatation but not due to leaflet tethering is associated with better outcome compared to organic etiologies.